PELAKSANAAN HAK REMISI BAGI WARGA BINAAN KASUS KORUPSI DALAM PRESPEKTIF HAK ASASI MANUSIA (Studi Pada Lembaga Pemasyarakatan Klas IIA Palu) - Moh Yusuf Hasmin; Andi Nurul Isnawidiawinarti Achmad (Fakultas Hukum Universitas Muhammadiyah Palu, 2018)
The tightening of remissions to corruption-assisted citizens in the Palu Class IIA Penitentiary does not reflect the protection of human rights values, where the remission is actually a right for inmates if they have carried out the conditions stipulated by Law Number 5 of 1995 concerning Corrections, the State must give the remission rights to inmates including those fostered by corruption cases if this is not given then the State violates human rights. know the legal impact of tightening remissions for residents fostered by corruption cases at Class IIA correctional facilities. By using the research method is empirical juridical which means the type of legal research that functions see the law in reality. Kata Kunci : Guided People. Corruption Case. Remission